Parental perceptions of barriers and facilitators to preventing child unintentional injuries within the home: a qualitative study - Ablewhite, Joanne; Peel, Isabel; McDaid, Lisa; Hawkins, Adrian; Goodenough, Trudy; Deave, Toity; Stewart, Jane; Kendrick, Denise (BioMed Central, 2015)
Background